Learning from Experience Volume II: Lessons from the U.S. Navy's Ohio, Seawolf, and Virginia Submarine Programs - Schank, John F. (RAND Corporation, 2011)
The U.S. Navy asked the RAND Corporation to develop a set of lessons learned from previous submarine programs that could help inform future program managers. This volume presents lessons from three U.S. submarine programs. The RAND team looked at how the programs were managed, the issues that affected management decisions, and the outcomes of those decisions. An overarching lesson from the three programs is the importance of program stability.